Waste Level and Cost Analysis of Steel Reinforcement Work in Construction Projects - Aditya Pradana; I Nyoman Dita Pahang Putra (TEKTONIK : Jurnal Ilmu Teknik, 2024)
The development of human needs in an area impacts increasing development in the construction industry sector. One of the problems that cannot be avoided from construction projects is the waste material generated during construction work. It is important to manage construction project waste properly to minimize the impact caused. Therefore, it is necessary to study the magnitude of the impact carried out in construction projects. This study aims to calculate the amount of waste level and cost of one of the construction wastes, namely reinforcing steel. The method used is a quantitative approach with the help of Microsoft Excel software. Shop Drawing is used as reference data in modeling the reinforcement shape and the purchase volume of reinforcing steel to determine the waste level and cost of steel reinforcement work planning. The results obtained are the percentage of waste level in the reviewed project of 10.15% and the percentage of waste cost of 7.39% of the total contract with a nominal waste cost of IDR 430,323,622. The percentage of waste level in this project is similar to several previous reference projects, which ranged from 4% to 13%.